MASS TRAPPING OF Anthonomus grandis Boheman WITH GRANDLURE - SUAREZ-GOMEZ, HERNANDO; CASTRO-ORTEGA, LUIS A. (Revista Colombiana de Entomología, 1990)
The registration during six years of the boíl weevil, Anthonomus grandis (Coleoptera: Curculionidae), populations using traps baited with Grandlure established that the highest capture rates were obtained when the traps were installed immediately after the destruction of the aerial part of the cotton remanents. Captures when the traps were set alone and in islands of cotton remanents were 444 to 808 adults, respectively; when the pheromone traps were set with traps crops, the result was 14.6 adults. A density of 1.3 traps/ha and a distance of 40 meters offered a good index of capture. The rain showed negative effects on the attraction action of the pheromone.